KETIDAKMAMPUAN INDONESIA DALAM MEMANFAATKAN BITCOIN DAN CRYPTOCURRENCY - Wibisono, Muhammad Gunawan (Department of International Relations, Brawijaya University, 2019)
Cryptocurrency is a new sector from the advantages digital economy concept. This sector form purely commodity and neutral from political invention. Because of the neutrality it become dangerous and prohibited for many countries cause the affection with central bank and currency stateKeywords: Cryptocurrency, Digital, Economy, Commodity, Political, State.